Phytochemical and cytotoxic investigations of the lichen Stereocaulon evolutum Graewe - Huyen, Vu Thi; Thu Tram, Nguyen Thi; Cuong, Nguyen Manh; Dam, Nguyen Phuc; Françoise, Lohézic-Le Dévéhat; Joël, Boustie (Vietnam Journal of Chemistry, 2017)
Lichens are fungal and algal/cyanobacterial symbioses resulting in the production of specific metabolites with a great variety of effects such as antibiotic, antimycobacterial, antiviral, anti-inflammatory, analgesic, antipyretic and antiproliferative. As a part of searching cytotoxic compounds from lichens, a phytochemical investigation was conducted on a squamulose lichen, Stereocaulon evolutum Graewe, collected in France. Five known compounds including atranorin (1), atranol (2), lobaric acid (3), ursolic acid (4), and methyl 3’-methyllecanorate (5) were isolated for the first time from such lichen. Their structures were elucidated by ESI-HR-MS, NMR spectral analysis and compared with literature data. Cytotoxicity screening of five isolated compounds were evaluated on seven cell lines including HuH7, CaCo-2, MDA-MB-231, HCT116, PC3, NCI-H727 and HaCaT. Compound (5) was found high cytotoxicity effect on all investigated cell lines while other compounds showed non-cytotoxic. Keywords. Lichen, Stereocaulon, atranorin, cytotoxicity.